Genetic and Non-Genetic Mechanisms of Resistance to BCR Signaling Inhibitors in B Cell Malignancies - Ondrisova, Laura; Mraz, Marek (Frontiers in Oncology, 2020)
The approval of BTK and PI3K inhibitors (ibrutinib, idelalisib) represents a revolution in the therapy of B cell malignancies such as chronic lymphocytic leukemia (CLL), mantle-cell lymphoma (MCL), diffuse large B cell lymphoma (DLBCL), follicular lymphoma (FL) or Waldenström’s macroglobulinemia (WM). However, these “BCR inhibitors” function by interfering with B cell pathophysiology in a more complex way than anticipated, and resistance develops through multiple mechanisms. In ibrutinib treated patients, the most commonly described resistance-mechanism is a mutation in BTK itself, which prevents the covalent binding of ibrutinib, or mutations in PLCG2, which acts to bypass the dependency on BTK at the BCR signalosome. However, additional genetic aberrations leading to resistance are still being described (such as mutations in the CARD11, CCND1, BIRC3, TRAF2, TRAF3, TNFAIP3, 6q and 8p chromosomal region loss, a gain of Toll-like receptor (TLR)/MYD88 signaling or gain of 2p chromosomal region). Furthermore, relative resistance to BTK inhibitors can be caused by non-genetic adaptive mechanisms leading to compensatory pro-survival pathway activation. For instance, PI3K/mTOR/Akt, NFkB and MAPK activation, BCL2, MYC, and XPO1 upregulation or PTEN downregulation lead to B cell survival despite BTK inhibition. Resistance could also arise from activating microenvironmental pathways such as chemokine or integrin signaling via CXCR4 or VLA4 upregulation, respectively. Defining these compensatory pro-survival mechanisms can help to develop novel therapeutic combinations of BTK inhibitors with other inhibitors (such as BH3-mimetic venetoclax, XPO1 inhibitor selinexor, mTOR or MEK inhibitors). The mechanisms of resistance to PI3K inhibitors remain relatively unclear, but some studies point to MAPK signaling upregulation via both genetic and non-genetic changes, which could be co-targeted therapeutically. Alternatively, drugs mimicking the BTK/PI3K inhibition effect can be used to prevent adhesion and/or malignant B cell migration (chemokine and integrin inhibitors) or to block the pro-proliferative T cell signals in the microenvironment (such as IL4/STAT signaling inhibitors). Here we review the genetic and non-genetic mechanisms of resistance and adaptation to the first generation of BTK and PI3K inhibitors (ibrutinib and idelalisib, respectively), and discuss possible combinatorial therapeutic strategies to overcome resistance or to increase clinical efficacy.